RAPID TURNOVER OF MCL-1 COUPLES TRANSLATION TO CELL SURVIVAL AND APOPTOSIS - Adams, Kenneth W. (2007)
Inhibition of translation plays a role in apoptosis induced by a variety of stimuli, but the mechanism by which it promotes apoptosis has not been established. We have investigated the hypothesis that selective degradation of anti-apoptotic regulatory protein(s) is responsible for apoptosis resulting from translation inhibition. Induction of apoptosis by cycloheximide was detected within 2 – 4 h and blocked by proteasome inhibitors, indicating that degradation of short-lived protein(s) was required. Caspase inhibition and overexpression of Bcl-x(L) blocked cycloheximide-induced apoptosis. In addition, cycloheximide induced rapid activation of Bak and Bax, which required proteasome activity. Mcl-1 was degraded by the proteasome with a half-life of approximately 30 min following inhibition of protein synthesis, preceding Bak/Bax activation and the onset of apoptosis. Overexpression of Mcl-1 blocked apoptosis induced by cycloheximide, while RNAi knockdown of Mcl-1 induced apoptosis. Knockdown of Bim and Bak, downstream targets of Mcl-1, inhibited cycloheximide-induced apoptosis, as did knockdown of Bax. Apoptosis resulting from inhibition of translation thus involves the rapid degradation of Mcl-1, leading to activation of Bim, Bak and Bax. Because of its rapid turnover, Mcl-1 may serve as a convergence point for signals that affect global translation, coupling translation to cell survival and the apoptotic machinery.